Targeted Therapy in NSCLC: A Comprehensive Review of Molecular Drivers and Treatment Strategies - Milasheuskaya, Valeryia; Miraniuk, Katsiaryna; Sobchynskyi , Mykola; Myrnyi , Andrii; Kowalczuk , Dmytro; Kasianik , Viktoryia; Lazitskaya , Darya; Turlej , Kamil; Kiełbaszewska , Iga; Surosz , Natalia; et al. (Quality in Sport, 2025)
Non-small cell lung cancer (NSCLC) remains a leading cause of cancer-related mortality worldwide, with its management increasingly guided by molecular profiling and targeted therapies. This review comprehensively examines current treatment standards for NSCLC, focusing on the evolving landscape of targeted therapies tailored to specific oncogenic driver mutations, including EGFR, ALK, ROS1, MET, KRAS, RET, BRAF, NTRK, and HER2. We highlight the efficacy, resistance mechanisms, and clinical trial outcomes of tyrosine kinase inhibitors (TKI) and other targeted agents, emphasizing their impact on progression-free survival (PFS) and overall survival (OS). The integration of these therapies into clinical practice has transformed patient outcomes, particularly in advanced-stage disease. However, challenges such as acquired resistance and toxicity profiles necessitate ongoing research into combination strategies and next-generation inhibitors. This work underscores the importance of precision medicine in NSCLC and outlines future directions for optimizing therapeutic approaches.